Unraveling the Complex Features of the Seismic Scatterers in the Mid‐Lower Mantle Through Phase Transition of (Al, H)‐Bearing Stishovite - Yu, Yingxin; Zhang, Youyue; Li, Luo; Zhang, Xinyue; Wang, Denglei; Mao, Zhu; Sun, Ningyu; Zhang, Yanyao; Li, Xinyang; Li, Wancai; Speziale, Sergio; Zhang, Dongzhou; et al. (Geophysical research letters, 2025)
Small‐scale scatterers observed in the mid‐lower mantle beneath the subduction zones are thought to result from the phase transition of stishovite within subducted oceanic crusts. Here we investigate the phase transition of (Al, H)‐bearing stishovite with four compositions at simultaneously high P‐T conditions combining Raman spectroscopy and X‐ray diffraction. These experimental results reveal that the incorporation of 0.01 a.p.f.u Al into stishovite with H/Al ratio of ∼1/3 lowers the transition pressure by 6.7(3) GPa. However, the Clapeyron slope of this transition is nearly unaffected by changes in the Al content and has a value of 12.2–12.5(3) MPa/K. According to our results, Al content variation ranging from 0 to 0.07 a.p.f.u in SiO2 can reasonably explain the depth distribution from 800 to 1,900 km of the seismic scatterers observed in the circum‐Pacific region. These results deepen our understanding on the complex features of mid‐lower mantle seismic scatterers and corresponding dynamic processes. Plain Language Summary Seismic studies have identified various small‐scale scatterers in the mid‐lower mantle, with low‐VS and complex depth variations between 700 and 1,900 km. Understanding the formation mechanisms of these scatterers is crucial for understanding mantle dynamics and chemical evolution. Previous studies suggest that their formation is linked to the structural phase transition of SiO2 from stishovite to post‐stishovite in subducted oceanic crusts, with variations in Al and H content potentially influencing the transition depth. However, earlier experiments on (Al, H)‐bearing stishovite phase transition were conducted only at high pressures and 300 K, limiting our ability to quantify the relationship between variations in subducted oceanic crust composition and small‐scale scatterers in the lower mantle. In this study, we investigate the phase transition of (Al, H)‐bearing stishovite under simultaneously high pressure and temperature conditions. Our results constrain how variations in Al and H content and temperature affect the transition depth. The obtained experimental results can be used to determine the depth of the post‐stishovite phase transition with varying Al content at different temperatures and provide critical experimental evidence for understanding the formation and corresponding dynamic processes of small‐scale scatterers in the lower mantle. Key Points The phase transition of (Al, H)‐bearing stishovite are comprehensively investigated under simultaneously high P‐T conditions Al and H incorporation into stishovite significantly lowers the transition pressure at 300 K but minimally affects the Clapeyron slope Al content variation from 0 to 0.07 a.p.f.u in SiO2 can explain the depth distribution of seismic scatterers in the circum‐Pacific region